Answer:
Vertex = (-1,4).
Explanation:
Given equation is
.
Now we need to find the vertex of the graph of given function
.
To find that we can rewrite given function into vertex form
![y=-(x-1)(x+3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8dfth2gushl8ljp81nj4qt4gu7vcd4pxgq.png)
![y=-(x^2+3x-1x-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lmticz9mkuwbnye7lm4501xnqf5e11pvsu.png)
![y=-(x^2+2x-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uu8x5p1fcm5dlinvf9ftnxlcs5iqk39apa.png)
![y=-(x^2+2x+1-1-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7fqr7eaj6u0g56cmoxj4was8c7zodxijsj.png)
![y=-((x+1)^2-1-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/llfrw8ml2zcv2b086ppf7su507u23dfcp1.png)
![y=-((x+1)^2-4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1bmexhekvpdgcje9uo6uxylgn9tsk4goun.png)
![y=-(x+1)^2+4](https://img.qammunity.org/2020/formulas/mathematics/college/1xevup8noako7co9s8gu8t95cx4hvebbyq.png)
Now compar this equation with
![y=a(x-h)^2+k](https://img.qammunity.org/2020/formulas/mathematics/high-school/7xiq973pej7bis77rj649g420rebwvc4wx.png)
we get: h=-1, k=4
Hence vertex is (h,k) or (-1,4).